Implementing the 2030 Agenda in Pakistan: the critical role of an enabling environment in the mobilisation of domestic and external resources - Murad Ali (Deutsches Institut für Entwicklungspolitik (DIE), 2017)
This study examines the role of an “enabling environment”, an atmosphere of good governance and effective public financial management (PFM), in mobilising resources needed for the implementation of the ambitious 2030 Agenda for Sustainable Development. Achievement of the 17 Sustainable Development Goals (SDGs) requires substantial financial resources, and generation of those resources is largely contingent on the presence of an enabling institutional and policy environment. If an environment of good governance with effective PFM institutions can be ensured, the domestic and external resources necessary for the achievement of the SDGs can be mobilised. In environments where PFM systems are ineffective, corruption is rampant, and transparency and accountability are minimal, it is unlikely that sufficient resources for sustainable development will be mobilised. There are four principal financing sources: domestic, international, public and private. While the sources have grown in recent years, they are still markedly less than adequate for successful implementation of the 2030 Agenda. This paper first assesses the centrality of enabling environments for sustainable development at the global level, then applies the framework to a Pakistan case study. The operationalisation and implementation of the 2030 Agenda is examined at the country level by analysing the implications of an enabling environment, or lack thereof, for domestic resource mobilisation (DRM) and for attracting foreign financing in the form of development cooperation and foreign direct investment (FDI). In view of the overall strong link between an enabling environment and its potential for resource mobilisation in developing countries, including Pakistan, there is a need for consistent locally-driven efforts and strong political will to improve the quality of governance and create an environment that is conducive to resource generation for the successful implementation of the 2030 Agenda.
Keywords: 330